2015
DOI: 10.1016/j.rasd.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Synergic effect of GSTP1 and blood manganese concentrations in Autism Spectrum Disorder

Abstract: We used data from 100 age- and sex-matched case-control pairs (age 2–8 years) from Jamaica to investigate whether there is an interaction between glutathione-S-transferase (GST) genes and blood manganese concentrations (BMC) in relation to Autism Spectrum Disorder (ASD). Our findings, indicate that among children who had the Ile/Ile genotype for GST pi 1 (GSTP1), those with BMC ≥ 12µg/L had about 4 times higher odds of ASD than those with BMC < 12µg/L, (P=0.03) under a co-dominant genetic model. After adjustin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 62 publications
4
36
0
Order By: Relevance
“…The contribution of Mn for the other GSTP1 genotypes (Ile/Val and Val/Val) was not strong (i.e., <0.2) for both positive and negative models. This finding is consistent with the results from the analysis where interactive effect between Mn and GSTP1 in relation to ASD was tested without or with adjustment of other four metals in the ERAJ study (Rahbar et al., , ), which showed that higher Mn concentrations were significantly associated with ASD for only the GSTP1 Ile/Ile genotype, but this significant association was not found among children with Ile/Val or Val/Val.…”
Section: Application To the Epidemiological Research On Autism Spectrsupporting
confidence: 90%
See 2 more Smart Citations
“…The contribution of Mn for the other GSTP1 genotypes (Ile/Val and Val/Val) was not strong (i.e., <0.2) for both positive and negative models. This finding is consistent with the results from the analysis where interactive effect between Mn and GSTP1 in relation to ASD was tested without or with adjustment of other four metals in the ERAJ study (Rahbar et al., , ), which showed that higher Mn concentrations were significantly associated with ASD for only the GSTP1 Ile/Ile genotype, but this significant association was not found among children with Ile/Val or Val/Val.…”
Section: Application To the Epidemiological Research On Autism Spectrsupporting
confidence: 90%
“…Since 2009, the research team at University of Texas Health Science Center at Houston (UTHealth), in collaboration with investigators at the University of the West Indies (UWI), have conducted two phases of an age‐ and sex‐matched case‐control study to investigate the role of the GST genes (e.g., GSTP1 ) and their potential interactions with five metals, lead (Pb), mercury (Hg), arsenic (As), cadmium (Cd), and manganese (Mn), in relation to ASD in Jamaica. Details on the recruitment and assessment procedures of this study have been reported previously (Rahbar et al., , , , , , , , ). So far, a significant gene‐environment interaction between GSTP1 and Mn was found when Mn was the only metal that was assessed (Rahbar et al., ).…”
Section: Application To the Epidemiological Research On Autism Spectrmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we found a significant gene-environment interaction between GSTP1 and blood manganese concentrations (BMC) indicating that among children who had the Ile/Ile genotype for GSTP1 , those with BMC ≥ 12 µg/L had about four times higher odds of ASD than those with BMC < 12 µg/L ( p = 0.03) [44]. …”
Section: Introductionmentioning
confidence: 99%
“…Saliva has also been used as a DNA source for epigenetic analysis in bipolar disorder and schizophrenia [51], for genetic analysis and investigation of the impact of nutritional intake and environmental toxins in ASD [52]. Most recently, Frank Middleton and colleagues used the salivary microRNA profiles for identification of children with ASD [53].…”
Section: Discussionmentioning
confidence: 99%